Roberto Morales-Harley, ‘The Embassy, the Ambush, and the Ogre: Greco-Roman Influence in Sanskrit Theater’ - Gitomer, David L. ca. 20./21. Jh. (Religions of South Asia, 2025)
Roberto Morales-Harley, The Embassy, the Ambush, and the Ogre: Greco-Roman Influence in Sanskrit Theater. Cambridge: Open Book Publishers, 2024. 271 pp., £35.95 (hb), £21.95 (pb), £5.99 (epub), free (PDF). ISBN 9781805113621 (hb), 9781805113614 (pb), 9781805113645 (epub), 9781805113638 (PDF).